Microsatellite Markers- A New Practice of DNA Based Markers in Molecular Genetics - Mittal, Neha; Dubey, Alok Kumar (Pharmacognosy Reviews)
Microsatellites are randomly interspersed within eukaryotic genomes. These are also known as SSRs (Simple sequence repeats), STRs (Short tandem repeats), STMs (Sequence tagged microsatellites), and VNTRs (Variable number of tandem repeats), are short 1-8 bp long monomer sequences, which randomly repeated in the DNA sequences. Conservation of the flanking sequence of each microsatellite locus allows the design of primers for PCR amplification. Then amplified products are separated by electrophoresis (either on high resolution agarose or acrylamide gels) to detect the polymorphism in repeat length. These markers don’t require the radioactivity for detection and these are extremely robust as well as easily exchanged between the laboratories. Multiplex reactions of SSRs can easily be run to speed up the assay, when the products have non-overlapping size ranges. Microsatellites have emerged as the marker of choice for plant genetic resources and molecular genetic applications due to their abundant and uniform distribution throughout the genome, highly variable nature with regard to repeat number, show codominant inheritance, ease of transferability and reproducibility, and found highly efficient in the DNA fingerprinting analysis, as well as can also be utilized in the pedigree analysis of different plant species. This marker system has been proven beneficial for crop improvement and for breeding applications in many species. These are also found the useful tools to detect the polymorphisms in low level of intraspecific diversity. Consequently, in the present review we have described the various characteristic features and properties of these highly polymorphic microsatellite markers, which found beneficial in several molecular genetic and breeding applications.
Keywords: Microsatellite markers; Molecular genetics; Amplification; PCR; SSRs